Agroforestry as Climate Change Mitigation - Budiastuti, Maria Theresia Sri (Future Science)
Climate change affects the existence of agricultural production from time to time, especially by increasing the concentration of CO2 in the atmosphere which has an impact on increasing temperatures. Temperature as an environmental factor influences plant physiological processes, which in turn affects plant production. In addition, climate change causes high fluctuations between the intensity of rain and drought, giving rise to La-Nina and El-Nino phenomena. This condition is a threat to food security and thus stakeholders are obliged to take concrete actions in the form of mitigating the impacts of climate change. Agroforestry is the first choice of agricultural cultivation technology by promoting trees as ecosystem service providers in the form of microclimate and soil (nutrients and water) which are beneficial for cultivated crops (seasonal). This cultivation technology also increases the potential of suboptimal land in Indonesia, which is quite extensive. Agroforestry systems improve suboptimal land quality and support climate change adaptation and mitigation efforts. Some food crops such as upland rice, soybeans and maize can be cultivated in agroforestry systems. Although the production of food crops in agroforestry systems is relatively lower than in open areas, agroforestry is considered to have the ability to support food security in terms of soil and water conservation, diversification of land use and the adequacy of micronutrients.